A Framework of Relational Information Control: A Review and Extension of Information Control Research in Interpersonal Contexts. Issue 2 (23rd February 2017) - Crowley, Jenny L.
Abstract: Research on information control in interpersonal contexts has grown in the last 30 years. Scholars have considered multiple manifestations of information control, including taboo topics, topic avoidance, privacy, and secrecy, as ways individuals withhold information. This paper reviews and presents limitations of the extant literature, including conflating different manifestations, privileging explicit acts, and presuming agency. The paper then addresses these limitations by proposing a new framework that articulates a process and typology of information control in relationships. The typology departs from existing research to categorize information control based on the perspectives of the sender and receiver. In so doing, the framework organizes several strands of research to offer a comprehensive approach to the study of information control in interpersonal contexts.